2014
DOI: 10.2337/db13-0939
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 Is a Major Negative Regulator of IRF4-Dependent Lipolysis Affecting Tregs in Adipose Tissue and Systemic Insulin Sensitivity

Abstract: Obesity elicits immune cell infiltration of adipose tissue provoking chronic low-grade inflammation. Regulatory T cells (Tregs) are specifically reduced in adipose tissue of obese animals. Since interleukin (IL)-21 plays an important role in inducing and maintaining immune-mediated chronic inflammatory processes and negatively regulates Treg differentiation/activity, we hypothesized that it could play a role in obesity-induced insulin resistance. We found IL-21 and IL-21R mRNA expression upregulated in adipose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 44 publications
4
59
0
Order By: Relevance
“…Other factors reported to influence VAT Treg accumulation include IL-21 (55) and Stat3 (56), both as negative regulators. Interestingly, Helicobacter pylori colonization of lean mice augments the VAT Treg population, diminishes the VAT inflammatory macrophage population, and improves systemic metabolic indices, via a PPARγ-dependent mechanism (57).…”
Section: Visceral Adipose Tissue Tregs: Regulators Of Organismal Metamentioning
confidence: 99%
“…Other factors reported to influence VAT Treg accumulation include IL-21 (55) and Stat3 (56), both as negative regulators. Interestingly, Helicobacter pylori colonization of lean mice augments the VAT Treg population, diminishes the VAT inflammatory macrophage population, and improves systemic metabolic indices, via a PPARγ-dependent mechanism (57).…”
Section: Visceral Adipose Tissue Tregs: Regulators Of Organismal Metamentioning
confidence: 99%
“…88 In addition, Kong et al 89 recently reported that IRF4 functions as a dominant transcriptional regulator of thermogenesis via its direct interaction with peroxisome proliferator-activated receptor gamma, coactivator 1 alpha (PGC-1α) to effectively enhance downstream antiobesity factors. As a negative mediator of diet-induced metabolic disorder, the increased expression of IRF4 also reasonably explains the antagonistic effect of IL-21 deficiency on metabolic deregulation, 120 potentially benefiting from a mechanism by which IL-21 inhibited the activation of the forkhead box O1 (FoxO1)-IRF4 axis via a fasting signal.…”
Section: Interferon Regulatory Factormentioning
confidence: 99%
“…In this issue, Fabrizi et al (9) demonstrate that mice lacking Il-21 are protected against high-fat diet–induced metabolic dysfunction. Il-21 is produced by Th17 cells, which in turn promotes expansion of Th17 cells and inhibits induction of Tregs (10).…”
mentioning
confidence: 99%
“…Fabrizi et al (9) demonstrate the ability of Il-21 to modulate metabolic homeostasis through inhibition of adipose tissue Tregs and Irf4-mediated lipolysis. However, these findings also raise several unanswered questions.…”
mentioning
confidence: 99%